A prospective study conducted in a tertiary care hospital in eastern Rajasthan on the function of a multimodal perioperative management protocol in colorectal cancer surgery - Verma, Pradeep Kumar; Dadhich, Yogendra; Khan, Farukh; Singh, Amit; Choudhary, Kanhaiya Lal (International Journal of Research in Medical Sciences, 2024)
Background: For colorectal surgery, the enhanced recovery after surgery (ERAS) group has conducted a thorough analysis of perioperative treatment. When combined, a series of operations known as colorectal resection result in a shorter duration of stay, fewer problems, and an early recovery of gut function. Until recently, it was considered typical to stay in the hospital for 10 to 14 days after a big bowel resection. This study aimed to study the effects of a multimodal perioperative care protocol in patients undergoing surgery for colorectal cancer in a tertiary care hospital in eastern Rajasthan, India. Methods: This was prospective randomized-controlled trial. Patients who are undergoing elective colorectal cancer surgery in tertiary care hospital (Sawai Man Singh hospital, Jaipur, Rajasthan) in year 2016 -17. Results: Hospital stays were 6.64±0.842 (median 6-9) and 8.25±1.52 (median 6-12) days (p=0.002) for 30 patients (n=14 in the multimodal group and 16 in the control group), respectively. Complication rates were 13.40% and 20.31% (p=0.019), 30-day readmission rates were 14.28% and 25% (p=0.029), and mortality rates were 7.14% and 12.5% in the multimodal and control groups. Conclusions: Complications, readmission rates, and death were all considerably lower in the multimodal group compared to the control group following the implementation of the multimodal perioperative treatment protocol during the hospital stay for colorectal cancer.